ASSESSING AND DEVELOPING STUDENTS’ ART SKILLS THROUGH DIGITAL PORTFOLIOS - Muratova Dilnavoz Jamshid qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
Digital portfolios have emerged as a powerful tool in contemporary art education for assessing and developing students’ artistic skills. These platforms allow learners to collect, organize, and present their creative work digitally, facilitating continuous assessment and reflection. This article examines the pedagogical potential of digital portfolios in enhancing students’ art competencies. The study explores how digital portfolios support individualized learning, enable formative assessment, and encourage self-reflection and creativity. The findings suggest that integrating digital portfolios into art education promotes skill development, motivates students, and fosters a learner-centered approach that enhances both artistic performance and critical evaluation skills.